A new nematicidal compound produced by Streptomyces albogriseolus HA10002 - Zeng, Qingfei (Springer Netherlands, 2013)
Strain HA10002 was isolated from mangrove sediment collected from Dongzhaigang Mangrove Reserve in Hainan, China. It was selected with potent nematicidal activity and was identified as Streptomyces albogriseolus. By bioassay-guided fractionation, a new active component A22-1(S1) against root-knot nematodes was separated from its fermentation broth. On the basis of spectroscopic analyses and comparison with the data from correlative literature, the structure of S1 was established to be 6′-methyl-fungichromin, named as fungichromin B in this paper. The LD50 values of fungichromin B to the 2-stage juveniles of Meloidogyne incognita and Meloidogyne javanica were 7.64 and 7.83 μg/ml, respectively. Further examination demonstrated fungichromin B still showed a wide antifungal spectrum, as with fungichromin.